The Influence of Knowledge, Skills, Attitude and Organization Commitment Using Ethical Climate as A Moderator Towards Ethical Decision Making of Accountants in Malaysia: A Conceptual Paper - Kanjanapathy, Malini; Ramakrishnan, Suresh (International Journal of Engineering and Technology, 2018)
The aim of this study is to investigate the influence of Knowledge, Skills, Attitude and Organization Commitment Using Ethical Climate as a moderator towards Ethical Decision Making of Accountants in Malaysia. Empirical research on ethical decision making of Accountants has shown that knowledge, skills and attitude are important factors in improving Accountants decision. However, literature on Accountants Ethical Decision Making in Malaysia has highlighted research gaps in few areas which is the use of Individual and Situational Moderators in measuring the Theorist of Ethical Behavior, The use of Personal Values to Measure Ethical Judgment, The effect of Organization Culture and Ethical Climate on Ethical Decision Making using Self-Efficacy as the Moderator. To fill this sequel of research gaps, this research tends to identify the effects of knowledge, skills and attitude and Organization Commitment using Ethical Climate as a Moderator to measure ethical decision making of Accountants. In doing so, this research use Theory of Planned Behavior. This study focus on the Big Four Accounting Firms in Malaysia. This is because the audit of the Transmille Company by Deloitte auditors has not lived up to the expectations of public. The positivistic research philosophy will be used to empirically test the formulated hypotheses. The study will use quantitative analysis approach and survey strategy to collect data by adapting established measurement tools for each construct in the conceptual model. Questionnaires results will be analyzed using SPSS software.Â